Privileged protection? Effects of suspect race and mental illness status on public perceptions of police use of force - Kahn, Kimberly Barsamian (Journal of experimental criminology, 2017)
This study experimentally examined the joint influence of suspect race and mental illness status on the public’s support for police use of force, and whether participants’ race and social attitudes moderated these findings.